The future of national intelligence how emerging technologies reshape intelligence communities - Hershkovitz, Shay 1976 (Security and professional intelligence education series (SPIES), 2022)
"The Future of National Intelligence: How Emerging Technologies Reshape Intelligence Communities provides a blueprint for the future of national intelligence agencies by exploring emerging technologies and collaborative strategies for intelligence gathering and managing data"